Leveraging Substitute Teachers as Educational Leaders - Marcedes Butler (Education Sciences)
This autoethnographic study explores the lived experiences of an advanced-degree holder and educator with expertise in leadership and education policy who worked as a substitute teacher in the Clark County School District. Despite my qualifications, I often felt underutilized and disconnected, revealing systemic barriers within the educational system. Using distributed leadership theory, I examine these challenges and uncover the untapped leadership potential of substitutes to make meaningful contributions to P-12 education. This study proposes actionable solutions, including substitute profile systems, comprehensive onboarding programs, and structured mentorship initiatives. The findings highlight the importance of shared leadership in fostering equity, professional growth, and workforce stability, offering practical insights into how substitutes can transition from temporary roles to integral contributors within educational systems.